Pachamanka - cantando por la libertad - Toth, Markus (Austria, 2017)
It is a documentary about a Chilean music band. Formed during the dictatorship of Pinochet, Pachamanka’s initial goal was to fight the regime and communicate the situation in Chile through music. After facing prison time and persecution, some band members were forced to leave the Chile and continue their musical journey in Uruguay, Spain, and Austria.
Keywords: Documentary films